A STUDY ON DEVELOPMENT AND CURRENT APPLICATION OF MOTION GRAPHIC IN TAIWAN’S POPULAR MUSIC - Chen, Chia Min; Chang, Yen Jung (PEOPLE: International Journal of Social Sciences, 2019)
With the advances in technology, the way of communications has become more diverse. Motion graphic combines graphic design, animation design, and film languages. Motion graphic is a new industry with intense performance styles and can be used in different media and platforms, such as commercials, music videos, film and television titles, web pages, and various display screen sizes, etc. Because motion graphic is a non-narrative time-based media, mostly it combines with music. The Taiwan 25th Golden Melody Awards introduced motion graphic design for the first time in 2014. This changed the monotony of past awards ceremony and reignited audience’s attention and discussion, as well as sparked a wave of motion graphic within the country. Through in-depth interviews with some industry experts, this study has defined the concept of motion graphic, analyzed its applications and development in popular music, and explored its future trends. The results of the study show that motion graphic is a cross-domain integration. With the appearance of interactive technology products, motion graphic strengthens the connection between the media and the audience, bringing different interactive experiences to the audience. The development of the Internet has also led to the spread of motion graphic due to high image quality, which has changed the speed of message dissemination and the way people listen to music. Because motion graphic has the advantage of actively transmitting messages, it has three main applications in popular music, which are music videos, concert video design, and the visual presentation of award ceremony. It is an inevitable trend that future music will be presented in the form of motion graphic.